2018
DOI: 10.1093/jxb/ery428
|View full text |Cite
|
Sign up to set email alerts
|

GhNAC83 inhibits corm dormancy release by regulating ABA signaling and cytokinin biosynthesis inGladiolus hybridus

Abstract: GhNAC83 inhibits corm dormancy release in Gladiolus hybridus by promoting ABA signaling and inhibiting CK biosynthesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 28 publications
(39 citation statements)
references
References 94 publications
2
35
0
Order By: Relevance
“…As an ABA binding factor, ABF2 often combines with AREB1 to form the AREB1/ABF2 transcription factor, which is the key factor downstream of the ABA signaling pathway [54,55]. In the process of bud dormancy, the expression of ABF2 is theoretically conducive to ABA signal transduction, thus maintaining bud endodormancy [6,56]. In this study, ABF2 showed a unimodal curve, which reached its peak on 9 January (Figure 10), suggesting that its high expression promoted the release of endodormancy in buds.…”
Section: Relationship Between Hormone Metabolism and Endodormancy Releasementioning
confidence: 99%
“…As an ABA binding factor, ABF2 often combines with AREB1 to form the AREB1/ABF2 transcription factor, which is the key factor downstream of the ABA signaling pathway [54,55]. In the process of bud dormancy, the expression of ABF2 is theoretically conducive to ABA signal transduction, thus maintaining bud endodormancy [6,56]. In this study, ABF2 showed a unimodal curve, which reached its peak on 9 January (Figure 10), suggesting that its high expression promoted the release of endodormancy in buds.…”
Section: Relationship Between Hormone Metabolism and Endodormancy Releasementioning
confidence: 99%
“…A single transformed YM4271(a) colony containing different truncated or mutated promoters [F1 to F4 and pFUS3 MUT (0.6kb), described above] was used for mating with EGY48(α) containing BPCs. Mating and selection procedures were described in Wu et al (2018). The interaction was judged by the growth of yeast on selection media on the third day.…”
Section: Yeast One-hybrid Screeningmentioning
confidence: 99%
“…Previous studies have shown that the NAC family is involved in regulating multiple hormone signaling pathways. GhNAC83 affects the dormancy of gladiolus bulbs by regulating ABA signal transduction and CTK biosynthesis [42]. The function of MADs-Box (DAM) is widely studied in perennials such as apples and pears.…”
Section: Tfs Involved In Dormancy Releasementioning
confidence: 99%